The IMPLEMENTATION WAYPOINT SISTEM OF CIA COMBAT ROBOT VERSION N2MR3 USING THE INTERNET OF THING (IoT) BASED ON RASPBERRY PI 4.0 - Setyawan, Ravinda Dharma; Purwanto, Bambang; Yoda, Vincensius Arga (Pustaka Poltekad, 2021)
Abstract - In the current era, technological progress is very influential for the defense system and the progress of a country to maintain the peace of the country, including Indonesia. In maintaining the integrity of the Unitary State of the Republic of Indonesia, a technological design is needed to maintain state sovereignty. To achieve success, the CIA's N2MR3 version of the robot design has a waypoint system that can be moved semi-autonomous to reduce personnel and material losses that have been experienced so far. The design of this combat robot uses an internet of thing (IOT) system that can be moved through a web server and controlled by an operator. This combat robot can also assist in reconnaissance, not also maintain the security and integrity of the Unitary State of the Republic of Indonesia, but can also carry out attacks by preventing personnel losses. The CIA version of the N2MR3 robot is an advanced tool made to have more helpful functions in terms of the military. In order to help maintain the integrity of the Unitary State of the Republic of Indonesia, this robot can be used to maintain the integrity of the Unitary State of the Republic of Indonesia in Indonesia.